Pengaruh Kualitas Pelayanan, Nilai Pelanggan, dan Customer Relationship Management terhadap Loyalitas Pelanggan: Studi Kasus pada JNE Express Plamo Garden - Ananda, Defi; Satriawan, Bambang; Windayati, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2023)
This research aims to identify the impact of service quality, customer value, and Customer Relationship Management on customer loyalty at JNE Express Plamo Garden. The approach employed in this research is a quantitative method. Population of the research encompassed JNE Express Plamo Garden customers in January and February 2022 with a total of 49,620 people. In this research, 100 participants constituted the sample size. Data collection method employed was distributing a questionaire to participants for analysis was conducted using multiple linear regression, to improved hypothesis. The finding of the research reveal Service Quality. Customer Value, Customer Relationship Management (CRM) all positively and significantly influence Customer Loyalty at JNE Express Plamo Garden. The probability value are 0.000, 0.002 and 0.033, respectively, all of which are less than 0.05. The value of R-squared 49.9%, Customer Loyalty at JNE Express Plamo Garden could be attribute to variable Service Quality, Customer Value, and Customer Relationship Management (CRM), while the remaining 50.1% is attributed various other factors.